Hydatid Cyst Disease among Patients hospitalized at Baghdad teaching hospital: clinico-epidemiological study - Thabit, Maral F.; Abd Al- Latif, Qusay; Khursheed, Jihad Khder (AL-Kindy College Medical Journal, 2014)
Background. Echinococcosis/ hydatitdosis is a zoonotic parasitic disease caused by the infestation of the larval form of the tapeworm of the genus Echinococcus .The Liver, lungs, and kidneys are the common areas of infestation.Objectives: To describe hydatid disease in hospitalized patients from a clinico-epidemiological perspectives.Methods:: A retrospective study was conducted over a period of 6 months extending from 15th of November 2011 to the 15th of May 2012 by reviewing records of 125 patients who were hospitalized at Baghdad Teaching Hospital during 2011and received medical and surgical treatment for hydatid cyst disease. The information covered the socio-demographic and clinical characteristics of the patientsResults:.The present study included 40(32%) males and 85(68%) females. The highest percentage was in the 3rd decade about 32(25.6%). The highest number of patients 87(69.6%), were from Baghdad city, 85(68%) of patients were referred from public departments, 106(85%) of patients had a negative family history for hydatid disease.Majority of patients 109(88%) were symptomatic. Abdominal pain was the most common presenting symptom in 104(95.4%) of symptomatic patients. The liver alone was affected in118 (94.4%) of patients.. The treatment was by medications alone in 125(100%) patients or with addition of surgical treatment 82(65.5%) of patients which was by conservative procedure (partial pericystectomy). The basic investigations needed were complete blood picture (CBP), liver function test( LFT), Ultrasound applied to all patients 125(100)%, chest x-ray CXR 75(60%), computerized tomographyCT 44(35%) while endoscopic retrograde cholangio- pancreatography ERCP was done in only1(0.8%) patientConclusions: Hydatidosis is still an important and persistent health problem in Iraq ,further studies are needed involving multi- hospitals covering all Iraqi governorates .